2016
DOI: 10.1186/s12888-016-1104-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional survey evaluating Text4Mood: mobile health program to reduce psychological treatment gap in mental healthcare in Alberta through daily supportive text messages

Abstract: BackgroundTo complement the oversubscribed counselling services in Alberta, the Text4Mood program which delivers daily supportive text messages to subscribers was launched on the 18th of January, 2016. This report presents an evaluation of self-reports of the impact of the program on the mental wellbeing of subscribers.MethodsAn online link to a survey questionnaire was created by an expert group and delivered via text messages to mobile phones of all 4111 active subscribers of the Text4Mood program as of Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
163
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(189 citation statements)
references
References 23 publications
22
163
4
Order By: Relevance
“…The trend for mean scores across the stress, depression, and anxiety scales to decrease in severity from younger to older age has potential implications for planning to meet mental health service needs during COVID-19. Innovative and cost-effective interventions such as supportive text messaging which are independent of geographic location, are free to the end user, do not require expensive data plans, and can reach thousands of people simultaneously [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] could be useful particularly to a younger age population who seem to be most impacted psychologically during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The trend for mean scores across the stress, depression, and anxiety scales to decrease in severity from younger to older age has potential implications for planning to meet mental health service needs during COVID-19. Innovative and cost-effective interventions such as supportive text messaging which are independent of geographic location, are free to the end user, do not require expensive data plans, and can reach thousands of people simultaneously [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] could be useful particularly to a younger age population who seem to be most impacted psychologically during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Technology-enhanced treatments, including text messages, for substance use disorders benefit from feedback about quit progress (Free et al, 2011) or factors that might predict lapses in abstinence (Chih et al, 2014). In addition, as an adjunct to psychological treatments, text messaging has been shown to increase individual’s ability to manage disorders associated with mood regulation (Agyapong et al, 2016). The findings of the present study suggest that future research in this area might also benefit from examining whether feedback about mood-related triggers or feedback about larger than typical variability in mood could be useful intervention targets.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies explored the effects of innovative tailored behavioral change methods for smoking cessation and demonstrated that they can contribute to a higher success rates [ 28 30 ]. Other studies showed that the delivery of tailored motivational messages using mobile phones as a platform could be an effective way to enable smoking cessation [ 31 35 ] as well as to impact other aspects of health, such as promoting physical activity and exercise [ 36 , 37 ], mental healthcare [ 38 ], and alcohol-related harm [ 39 ], among others. These tailored messages are usually pieces of text based on the user’s responses to certain questions, assessing their attitude, social support, self-efficacy, and type of action planning.…”
Section: Introductionmentioning
confidence: 99%